Geekerella / 1. - Poston, Ashley (Once upon a con, 2017)
"Geek girl Ellie hopes to go to ExcelsiCon Cosplay to meet the actor (closet nerd Darien) scheduled to play Federation Prince Carmindor in a reboot of the movie 'Starfield'"--OCLC.